1996
DOI: 10.1111/j.1095-8649.1996.tb01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to handling in the turbot

Abstract: Turbot Scophthalmus maximus were cannulated via the afferent branchial artery and were either net-confined in sea water or in air for 9 min to monitor the stress response of a hatchery-reared marine flatfish. No mortality was observed. Aerial exposure appeared to mobilize plasma free fatty acids and stimulate the interrenal tissue but had no effect on circulating glucose or lactate levels. This pattern was qualitatively similar to that induced by net-confinement in sea water, although the magnitude and duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
30
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 30 publications
7
30
0
4
Order By: Relevance
“…In this dry stress experience, the results indicated that M. albus could respond quickly under air exposure stress by activating a series of physiological responses (AD and COR secretion), and then increase serum GLU content for meeting energy requirement and accelerate the synthesis of cholesterol to ensure COR secretion to adapt to the dry stress. The similar results was found in turbot (Waring, Stagg, & Poxton 1996) supplementation was significantly higher than the other groups at 2 and 24 hr. Serum T-SOD and CAT activities in the T 0.09 and T 0.15 groups had no significant difference with these in the FM group, while the T-SOD and CAT activities in the FM group was remarkably higher than that in the T 0 group at 2 hr.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this dry stress experience, the results indicated that M. albus could respond quickly under air exposure stress by activating a series of physiological responses (AD and COR secretion), and then increase serum GLU content for meeting energy requirement and accelerate the synthesis of cholesterol to ensure COR secretion to adapt to the dry stress. The similar results was found in turbot (Waring, Stagg, & Poxton 1996) supplementation was significantly higher than the other groups at 2 and 24 hr. Serum T-SOD and CAT activities in the T 0.09 and T 0.15 groups had no significant difference with these in the FM group, while the T-SOD and CAT activities in the FM group was remarkably higher than that in the T 0 group at 2 hr.…”
Section: Discussionsupporting
confidence: 87%
“…The similar results was found in turbot(Waring, Stagg, & Poxton 1996), sea bream (Pagrus major;Chopin, Arimoto, & Inoue 1996), greenback flounder (Rhombosolea tapirina;Barnett & Pankhurst, 1998) with the increase of the AD or COR secretion, and in coral trout (Plectropomus leopardus and Plectropomus maculatus; Frisch & Anderson 2005) with the increase of serum GLU content when the fish was under stress. Meanwhile, the body also improves antioxidant ability to strengthen its own protection.…”
supporting
confidence: 73%
“…1). In this respect, the sturgeon exhibited a more rapid response than the glycaemia elevation observed in turbot Scophthalmus marimus subjected to handling and multiple net confinements (Waring et al 1996;Waring et al 1997). The initial mean osmolality of 281.6 mOsm/kg rapidly increased, peaked at 288.3 mOsmkg within l h post-stress and then decreased.…”
Section: Blood Sampling Via Chronic Indwelling Cathetermentioning
confidence: 90%
“…This might be related to a higher energy output due to stress due to increased lipolysis of TGL to free fatty acids serving as energy source. Aerial exposure and net confinement of hatchery-reared turbot (Scophthalmus maximum L.) led to raised plasma-free fatty acid (FFA) levels instead of GL and lactate (Waring et al 1996). Despite the year-to-year differences in changes of glycid and lipid metabolisms of disturbed carp, a common trend is obvious: observed changes lead to mobilisation of energy reserves in fish disturbed by otter compared to the control group.…”
Section: Discussionmentioning
confidence: 88%